Inventory of landslide relics in Zhenxiong County based on human-machine interactive visual interpretation, Yunnan Province, China - Xue, Zhiwen; Xu, Chong; Zhang, Zhiqiang; Feng, Liye; Li, Hao; Zhang, Hourong; Zhu, Dengjie; Sun, Jingjing; Wang, Peng; Li, Lei; Chen, Jingyu (Frontiers in Earth Science, 2025)
IntroductionLandslides occur frequently in Zhenxiong County, posing significant threats to residents’ lives and property. A comprehensive understanding of the development patterns of landslide disasters in this region is crucial for disaster prevention, land-use planning, and risk assessment.MethodsThis study utilized high-resolution satellite imagery from the Google Earth Pro platform and employed a human-machine interactive visual interpretation approach to investigate landslide occurrences. A comprehensive landslide inventory comprising 3,979 landslide outlines was established through extensive literature review and data cleaning techniques. The spatial distribution characteristics and statistical patterns of landslides were analyzed.ResultsThe total landslide-affected area is 319.20 km2, with the largest landslide covering 4.55 km2 and the smallest measuring 1,779 m2. The average landslide area is 80,215 m2, with the majority (73.54%) classified as medium-sized landslides. The landslide area percentage (LAP) is 8.64%, and the landslide number density (LND) is 1.077 landslides per km2, with the highest recorded landslide density being 3.380 landslides per km2. Landslides are predominantly concentrated in four key areas: the confluence of the Baishui River and Yanxi River, Dashuigou Reservoir, both sides of the valley from Heitang Village to Hongyan Village, and Xiaogou Village. These areas are characterized by well-developed water systems, middle and low mountains, and heavily dissected landscapes.DiscussionThe landslide database established in this study provides essential scientific data for analyzing the spatial distribution of landslide disasters in Zhenxiong County. It offers valuable insights for local governments and relevant authorities in disaster prevention, land-use planning, and risk assessment. The findings highlight the significant impact of complex terrain and developed water systems in middle and low mountain regions on landslide disasters. Future studies should further integrate geological and meteorological factors for deeper analysis.